The Effect of Hypnobreasfleeding on Breast Milk Production at Gunung Maria Hospital - Pingkan Gloria Banibi; Anik Sri Purwanti (Institut Kesehatan Pelamonia, 2026)
Background: Adequate breast milk production is essential to support optimal infant growth and development. However, many postpartum mothers experience insufficient milk production due to psychological stress, anxiety, and lack of confidence during the breastfeeding process. Hypnobreastfeeding is a relaxation-based technique that combines hypnosis and positive affirmations to improve maternal comfort, reduce stress, and stimulate the hormones involved in breast milk production. Objective: This study aimed to determine the effect of hypnobreastfeeding on breast milk production among postpartum mothers at Gunung Maria Hospital. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 30 postpartum mothers who met the inclusion criteria and were selected using total sampling. Hypnobreastfeeding was provided according to a standardized procedure. Breast milk production was measured before and after the intervention. Data analysis was conducted using the Wilcoxon signed-rank test. Results: The results showed a significant increase in breast milk production after the implementation of hypnobreastfeeding. Statistical analysis using the Wilcoxon test revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of hypnobreastfeeding on breast milk production. Conclusion: Hypnobreastfeeding has a significant effect on increasing breast milk production among postpartum mothers at Gunung Maria Hospital. This intervention can be recommended as a complementary and non-pharmacological approach to support breastfeeding success.